2015
DOI: 10.1016/j.jcat.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of zeolite acid sites in NO/O2 mixtures and the catalytic properties of the new site in NO oxidation

Abstract: The NO oxidation reaction kinetics over a number of zeolite structures were investigated at temperatures above 423 K using plug-flow microreactors and in situ FTIR spectroscopy. Fast catalytic NO oxidation rates (up to 1,000 ×) are observed over Hand Na-exchanged zeolite frameworks (BEA, MFI, and CHA) at temperatures above 423 K with respect to the gas-phase reaction. NO oxidation rates increase with temperature over Hand Na-zeolites, while siliceous zeolites display little activity. Activation energies scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 76 publications
2
31
0
Order By: Relevance
“…12,13 Previous mechanistic studies of the NH3-SCR reaction indicated that the NO + species formed in zeolite pores play a significant role. [14][15][16] Szanyi et al…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Previous mechanistic studies of the NH3-SCR reaction indicated that the NO + species formed in zeolite pores play a significant role. [14][15][16] Szanyi et al…”
Section: Introductionmentioning
confidence: 99%
“…NO oxidation is also observed on zeolites due to confinement effects, which are studied separately with Reactive Forcefield (ReaxFF) molecular dynamics (MD) simulations at a realistic operating temperature of PNAs. 10,11 Experimental studies conducted with water as the co-feed suggest a negative impact of water on the activity of PNAs. 1−3 Moreover, theoretical calculations carried out by Mandal et al in the presence of water suggest a decrease in the NO binding energies.…”
Section: Introductionmentioning
confidence: 99%
“…The peak at around 2165 cm −1 is assigned to NO + adsorbed on acid Brønsted sites in the zeolite framework. This surface species has previously been reported to absorb IR in the region of 2220-2128 cm −1 for different types of zeolites [7,[26][27][28]30,31]. The intensity of IR absorbance in this region significantly decreased for PdLTA after 900 • C hydrothermal aging.…”
Section: Characterizationmentioning
confidence: 52%